Makna MAKNA TEOLOGIS UPACARA PENGHORMATAN SALIB PADA JUMAT AGUNG - Antonius P Sipahutar; Putra Rinduan Hulu (STP St. Bonaventura Medan, 2026)
The veneration of the cross on Good Friday constitutes a central rite in the liturgy of the Catholic Church, making present the mystery of Christ’s passion and death as the heart of Christian faith. In pastoral practice, however, this rite is often understood primarily as a personal devotional act or merely a liturgical custom without sufficient liturgical-theological reflection. This article analyzes the veneration of the cross within the framework of liturgical theology as a locus theologicus, highlighting its soteriological, participatory, kerygmatic, ecclesial, and eschatological dimensions. Employing a qualitative approach through library research, the study engages Sacred Scripture, magisterial documents, and relevant theological literature. The findings demonstrate that the veneration of the cross is not simply an expression of individual piety but an anamnetic and performative ecclesial act that actualizes faith in Christ’s redemptive work, enables participation in His passion, proclaims divine love manifested on the cross, and fosters eschatological hope. Consequently, the rite affirms the liturgy as an action of Christ and the Church, shaping the soteriological awareness and ecclesial identity of the faithful while encouraging conscious and active participation in the Paschal Mystery. Key words: Good Friday; veneration of the cross; anamnesis; redemption.